Analisis Stilistika Puisi Perempuan Penyair dalam E-PAPER Pikiran Rakyat Edisi Maret-Desember 2020 - Sekar Arum Fitri Hapsari (Universitas Singaperbangsa Karawang, 2022)
This research was made with the background of students' low knowledge of figurativelanguage, many students still make mistakes in understanding and using figurativelanguage. In addition, students' lack of knowledge of newspaper literature. The purposeof making this thesis is to describe the stylistic analysis of female poets' poetry in the epaper of the People's Thoughts March-December 2020 edition. Based on that, thisresearch is a qualitative research with analytical descriptive method. The subject in thisstudy is stylistic analysis (language style) using Nurgiyantoro's theory while the objectof research is the poetry of women poets in the e-paper of the People's Mind edition ofMarch-December 2020. The data analysis technique used is interactive analysistechnique, namely data reduction, data presentation, and analysis. conclusion. Thistechnique is accompanied by note-taking and reading techniques. Data reduction,namely the stage where the researcher records all the data found and in accordance withwhat is being studied when reading and interpreting the entire contents of the e-paperpoems of the People's Mind. This stage requires the process of reading repeatedly.Presentation of data, after the data has been successfully reduced, then the data isdescribed according to the theory used. Drawing conclusions, namely the stage wherethe data that has been presented earlier will be concluded. The results of the stylisticanalysis in the e-paper poems of the People's Mind are metaphor (12), personification (12), allegory (6), hyperbole (3), simile ( 2), irony (3), paradox (2), anaphora (1),parallelism (1), litotes (1).